HEALING OF PURULENT-INFLAMMATORY WOUNDS OF THE MAXILLOFACIAL AREA - Jakhongir Kholmuradov; Ortikali Tursunkulov (TADQIQOTLAR.UZ, 2025)
Abstract:  Purulent-inflammatory  wounds  in  the  maxillofacial  region  pose significant  challenges  due  to  their  complexity  and  proximity  to  vital  anatomical structures. The management and healing of these wounds require a comprehensive understanding  of  infection  control,  tissue  regeneration,  and  appropriate  therapeutic interventions. This article discusses the stages of wound healing, modern management strategies, and emerging therapies that enhance recovery and reduce complications.